‘Can you have your cake and eat it?’ A small-scale exploratory study of the influence of neoliberalism in managerial practices at private LTOs in China - Liu, Siwei (2020)
This study explores the aspects of Director of Studies (DOS) and owners’ managerial practices that are influenced by neoliberalism at five private Language Teaching Organisations (LTO) in shadow education industry in urban China. Shadow education is the after-school private tutoring sector which has both huge market size and intense competition. Management are responsible for the LTO’s business viability and their managerial practices are susceptible to neoliberal profit orientation. The ‘cake’ indicates the economic benefit, which can be viewed from both short-term and long-term perspective. Should the management focus on imminent gains to eat their ‘cake’ now or should they starve for the moment and enjoy the ‘cake’ in the future which may never come is truly a dilemma.